2012
DOI: 10.1038/ncomms2241
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the occurrence of submicroscopic malaria infections and their relevance for control

Abstract: Malaria parasite prevalence in endemic populations is an essential indicator for monitoring the progress of malaria control, and has traditionally been assessed by microscopy. However, surveys increasingly use sensitive molecular methods that detect higher numbers of infected individuals, questioning our understanding of the true infection burden and resources required to reduce it. Here we analyse a series of data sets to characterize the distribution and epidemiological factors associated with low-density, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
662
1
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 546 publications
(726 citation statements)
references
References 55 publications
49
662
1
14
Order By: Relevance
“…Similarly, the performance of rapid tests has been shown to decline with increasing transmission intensity [89], suggesting that people living in high-transmission areas may acquire immunity and control infections to densities below the detection threshold of standard diagnostic techniques. However, the relationship between transmission and parasite density seen on smaller scales is not observed over larger geographical areas, where lower endemicity has been related to a larger proportion of submicroscopic infections [73]. Such a high carriage of infections below the threshold of microscopic detection in areas of low transmission could be explained by the persistence of residual immunity in areas of low transmission, which keeps parasite density at submicroscopic levels [5], or fewer infections to overwhelm the immune response.…”
Section: Immune Resistance To Malariamentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, the performance of rapid tests has been shown to decline with increasing transmission intensity [89], suggesting that people living in high-transmission areas may acquire immunity and control infections to densities below the detection threshold of standard diagnostic techniques. However, the relationship between transmission and parasite density seen on smaller scales is not observed over larger geographical areas, where lower endemicity has been related to a larger proportion of submicroscopic infections [73]. Such a high carriage of infections below the threshold of microscopic detection in areas of low transmission could be explained by the persistence of residual immunity in areas of low transmission, which keeps parasite density at submicroscopic levels [5], or fewer infections to overwhelm the immune response.…”
Section: Immune Resistance To Malariamentioning
confidence: 94%
“…However, asymptomatic malaria infections are common in humans living in endemic areas [2], even in low-transmission settings [72], with prevalences four to five times higher than clinically patent infections. Although asymptomatic cases generally correlate with lower-density infections [73] and lower rates of infecting mosquitoes [74], the extended longevity of asymptomatic parasitemia expands the risk of transmission during much of this time and overall it constitutes a high proportion of transmission [74], possibly greater than that derived from clinical malaria cases [75]. Estimates of the burden of asymptomatic malaria depend on the method used to detect infecting parasites and the criteria for the definition of an asymptomatic episode [42].…”
Section: Box 1 Asymptomatic Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in areas where malaria prevalence is below 10% as measured by nucleic acid tests (NATs) such as the PCR, the majority (88%) of the infections cannot be detected by expert microscopy [40]. Such submicroscopic parasitaemia contributes substantially to malaria transmission [41,42], and although their attribution to a febrile illness has not been well characterized, such a possibility exists [43,44]. The contribution of submicroscopic infections to malaria transmission and febrile illness is likely to increase with declining malaria burden as a result of lowered naturally acquired immunity to malaria [45].…”
Section: Challenges Related To Parasite Diagnosis In Clinical Settingmentioning
confidence: 99%
“…The situation is likely to be more worse when malaria transmission and prevalence are progressively reduced because clients would continue to attend to health facilities on account of non-malarial causes of febrile illnesses [70]. While the adoption of mRDTs has significantly reduced the syndromic management of malaria, the mRDTs may not be sensitive and robust enough to detect low level and asymptomatic infections as malaria declines to low endemicity [41], hence the need to invest in the more robust and sensitive tests such as the NATs [51]. The NATs depend on the PCR, which is the most accurate method for the diagnosis of malaria parasites but this requires expensive equipment and reagents, highly trained laboratory personnel, and has long turnaround time.…”
Section: Possible Approaches To Address the Challengesmentioning
confidence: 99%